Knowledge, attitude, and practice of waste handlers about medical waste management in Debre Markos town healthcare facilities, northwest Ethiopia - Deress, Teshiwal (BMC Res Notes, 2019)
OBJECTIVE: Medical waste is a total waste stream which is generated from the healthcare facilities during the healthcare delivery process. It can contain potentially hazardous substances for the human being and the environment. Waste handlers play a significant role for its proper management and they need to have adequate knowledge, attitude, and practices. The study aimed to evaluate the knowledge, attitude, and practices of waste handlers regarding medical waste management in Debre Markos town healthcare facilities, northwest Ethiopia. RESULTS: A total of 55 medical waste handlers were studied from 12 healthcare facilities. Among this, 25 (45.4%) were diploma and certificate holders. The majority (69.1%) of the study participants were not provided with proper training. There was a lack of personal protective devices and waste management equipment supply. Regarding knowledge, attitude, and practices, 25 (45.5%), 43 (78.2%), and 44 (80%) of the study participants had adequate knowledge, favorable attitude, and adequate practice scores, respectively. There was high (30.9%) prevalence of needlestick and sharps injuries. Healthcare facilities should provide periodic training and adequate supplies for the waste handlers. Further study should be conducted on a large scale by including different levels of health facilities and regions of the country. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4174-7) contains supplementary material, which is available to authorized users.